2021
DOI: 10.3389/fgwh.2021.628625
|View full text |Cite
|
Sign up to set email alerts
|

Access to and Quality of Healthcare for Pregnant and Postpartum Women During the COVID-19 Pandemic

Abstract: Introduction: During the COVID-19 pandemic, obstetric care has adopted new precautions to ensure services can be maintained for pregnant women. The aim of this study was to describe access to and quality of obstetric care for pregnant and postpartum women during the COVID-19 pandemic and to identify factors that predict quality of care at this time.Methods: Between May 3 and June 28, 2020, we recruited women who were pregnant or within the first 6 months after delivery to participate in an online survey. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 37 publications
2
40
0
3
Order By: Relevance
“… 5 , 6 However, it is higher than responses found by Brislane et al in an online, global survey, where mean subscale responses on the same instrument (Quality of Prenatal Care Questionnaire) ranged from 3.4 to 4.1. 3 It is possible that respondents in single health system studies tended to rate their quality higher compared to respondents recruited online from a general population. Population average responses remained high (∼5) for all subscales in our study; however, several participants endorsed poor quality indicators including feeling rushed, that the provider was rude, and that test results were not explained in a way they could understand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 6 However, it is higher than responses found by Brislane et al in an online, global survey, where mean subscale responses on the same instrument (Quality of Prenatal Care Questionnaire) ranged from 3.4 to 4.1. 3 It is possible that respondents in single health system studies tended to rate their quality higher compared to respondents recruited online from a general population. Population average responses remained high (∼5) for all subscales in our study; however, several participants endorsed poor quality indicators including feeling rushed, that the provider was rude, and that test results were not explained in a way they could understand.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Health systems implemented a wide variety of changes to obstetric care, including the introduction of telehealth, limits on support persons at delivery or prenatal visits, and reduced-frequency prenatal visits. 2 , 3 Emerging evidence shows that reduced-frequency in-person prenatal care visits during the pandemic were not associated with worse birth or obstetric outcomes. 2 , 4 One survey conducted in a privately-insured Michigan suburban health system suggests most patients found that virtual visits were lower quality than in-person care (72.9%) but reported satisfaction with the visits (77.5%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that women would benefit from guidance on birth options, COVID-19 risks and safety, general pregnancy-related information, and coping with postpartum loneliness. 31 More knowledge about the quality of prenatal care could lead to targeted interventions and resources to ultimately improve maternal and child health among Black families. The investment in ensuring access to prenatal care in the United States may need to pivot to embrace assurance of quality alongside quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women have experienced fears of infection, especially at hospitals ( Davis-Floyd et al, 2020 ; Goyal et al, 2021 ), and anxiety about potential difficulties accessing medical care ( Overbeck et al, 2020 ). Many women have experienced some curtailment of in-person care appointments ( Altman et al, 2021 ; Blankstein Breman et al, 2021 ; Brislane et al, 2021 ; Goyal et al, 2021 ) and changes to the frequency of checkups ( Montagnoli et al, 2021 ; Rudrum, 2021 ). Many women have reported anxieties about changeable hospital policies that restricted the presence of support persons during delivery and enforced isolation during labor and after birth ( Blankstein Breman et al, 2021 ; Brislane et al, 2021 ; Davis-Floyd et al, 2020 ; DeYoung & Mangum, 2021 ; Gutschow & Davis-Floyd, 2021 ; Rudrum, 2021 ).…”
Section: Introductionmentioning
confidence: 99%